Ginger Stew Vs Warm Compress Toward Dysmenorrhea Intensity In Adolescent; Experimental Study - Handajani, Sih Rini; Sari, Lutfiana Puspita; Ambarsari, Elisha Ayu (Poltekkes Kemenkes Surakarta, 2023)
Background: Adolescence can be defined as a developmental phase characterized by the transition from childhood to adulthood, usually during this period marked by changes in physiology, psychology, mental, emotional, and social. The transition signs in females indicate that they are experiencing menstruation. Menstruation can cause dysmenorrhea in some individuals, leading to disruptions in their daily activities. Ginger stew compress, or warm compress, is a non-pharmacological therapy that can help alleviate dysmenorrhea. Methods: This was quantitative research using a quasi-experiment design with a two-group pretest-posttest approach. The participants were selected using a simple random sampling technique, resulting in a sample of 44 respondents divided into two groups. The instrument in this study was an observation sheet containing the identity of the respondent, and the scale to determine the level of pain intensity experienced was the Numeric Rating Scale (NRS). Results: This research indicates that there was a significant difference in dysmenorrhea intensity when using a ginger stew compress compared to a warm compress. The statistical analysis used was an independent sample t-test performed in the study with a p-value that was lower than 0.05 (Asymp.Sig 2-tailed = 0.015), indicating a significant difference between the two types of compresses, giving a ginger stew compress and a warm compress toward the intensity of dysmenorrhea. Conclusion: The ginger stew compress is more effective than the warm water compress to reduce the intensity of dysmenorrhea in adolescent girls in grade 7 at 2 JHS Gantiwarno. It is hoped that the results of this research can be utilized as an additional reference regarding research on treating menstrual pain with boiled ginger water compresses and warm compresses.